A non-mutated TROP2 fingerprint in cancer genetics - Guerra, Emanuela; Di Pietro, Roberta; Stati, Gianmarco; Alberti, Saverio (Frontiers in Oncology, 2023)
The advent of high throughput DNA sequencing is providing massive amounts of tumor-associated mutation data. Implicit in these analyses is the assumption that, by acquiring a series of hallmark changes, normal cells evolve along a neoplastic path. However, the lack of correlation between cancer risk and global exposure to mutagenic factors provides arguments against this model. This suggested that additional, non-mutagenic factors are at work in cancer development. A candidate determinant is TROP2, that stands out for its expression in the majority of solid tumors in human, for its impact on the prognosis of most solid cancers and for its role as driver of cancer growth and metastatic diffusion, through overexpression as a wild-type form. The Trop-2 signaling network encompasses CREB1, Jun, NF-κB, Rb, STAT1 and STAT3, through induction of cyclin D1 and MAPK/ERK. Notably, Trop-2-driven pathways vastly overlap with those activated by most functionally relevant/most frequently mutated RAS and TP53, and are co-expressed in a large fraction of individual tumor cases, suggesting functional overlap. Mutated Ras was shown to synergize with the TROP2-CYCLIND1 mRNA chimera in transforming primary cells into tumorigenic ones. Genomic loss of TROP2 was found to promote carcinogenesis in squamous cell carcinomas through modulation of Src and mutated Ras pathways. DNA methylation and TP53 status were shown to cause genome instability and TROP gene amplification, together with Trop-2 protein overexpression. These findings suggest that mutagenic and the TROP2 non-mutagenic pathways deeply intertwine in driving transformed cell growth and malignant progression of solid cancers.